Flavonoid Glucosides from Biota semipervirens - Atehar, Sajjad; Andrabi, S.M.A.; Qureshi, M. (Asian Journal of Chemistry, 2010)
An isoflavone glucoside, tectorigenin-4´-glucoside together with tectoridin, tectorigenin were isolated from leaves of Biota semipervirens. The structures of the compounds were established by spectroscopic and chemical methods.